A POSTCOLONIAL ANALYSIS OF THE MAIN CHARACTER IN THE ENGLISH NOVEL THE RELUCTANT FUNDAMENTALIST (2007) BY MOHSIN HAMID - Helendra, Helendra (Department of English Education of STAIN Jurai Siwo Metro, 2015)
Abstract: This study was aimed at getting the description of Changezâs character in the novel âThe Reluctant Fundamentalistâ based on Hybridity Theory of postcolonial analysis and in order to find out how is Hybridity and the hybrid identity affect the character of Changez, since the writer assumes that the character has undergone the hybrid identity. This was a qualitative study with descriptive analysis method in analyzing the Changez Character of the novel. The research used verbal data; such as texts as the basic analysis and in solving the research problems. The analysis shows that the novel idealized the hybrid nativeâs representation. Through the narrator protagonist, hybrid identity is indicated as a reconstruction process of native identity after the experience of colonization. The process can be seen through the ways the narrator protagonist positions himself within his painful memories, in attempt to comprehend the tradition and Europe as parts of his identity. As a critique of essentialism, in the novel is in a frame of resistance against European(America) domination.Keywords: postcolonial analysis, hybridity, characterizationÂ